2022 Annual trends and outlook report: Agrifood processing strategies for successful food systems transformation in Africa - Jenane, Chakib; Ulimwengu, John M.; Tadesse, Getaw (AKADEMIYA2063, 2022)
The 2022 Annual Trends and Outlook Report generates evidence to guide the ongoing transformation of African food systems through well-concerted and targeted policy interventions in the agrifood processing sector. The report explores available and emerging evidence and knowledge in a wide range of policy areas related to the processing segment of agrifood value chains. It confirms the emerging opportunities for agrifood industrialization in Africa driven by increased urbanization and middle-income consumers, and sheds light on key areas for policymakers and partners to design policies and make investments that strengthen the sector and increase its capacity to provide healthy diets for all.